ANTIOXIDANT TEST AND PEEL-OFF GEL MASK FORMULATION EXTRACT OF RED SPINNING (Amaranthus tricolor L) LEAVES WITH VARIATIONS OF GELLING AGENT TYPES - Welly Setyawan; Supriyanto; Maulita Saraswati (Joseph: Journal of Science and Pharmacy, 2022)
Background: Antioxidants are substances that inhibit or prevent cell damage due to free radical oxidation. Red spinach leaves (Amaranthus tricolor L.) contain flavonoid compounds, saponins and tanins that have antioxidant potential. The purpose of this study was to determine whether red spinach leaf extract (Amaranthus tricolor L) with various types of gelling agent has antioxidant activity and can be used as a pee-off gel mask formulation.Purpose: This study formulated a gel peel-off mask formulation with a variety of gelling agents, HPMC base 1%, Na CMC 2%and PVA 14%, with the active ingredient 3.5% red spinach leaf extract. Concentrated ethanol extract was obtained by extracting using 96% ethanol solvent maceration. Furthermore, testing the activity with the DPPH method, identifying the phytochemical content and evaluating the peel-off gel preparations using physical test parameters.Antioxidant activity quantitative test with UV-VIS spectrophotometric DPPH method at a wavelength of 517 nm with a comparison of vitamin C. Method: From the research that has been done, it can be concluded that red spinach leaves can be formulated into the most stable peel-off gel mask, namely formula III with a PVA base of 14% with an IC value of 57.04μg/ml showing the strongest   antioxidant activity and closer to the test parameters gel masks and parameters against positive control.